The Reproduction Without Alterity of AI: LatamGPT as a Form of Dissent and Technological Reappropriation. - Pizarro Contreras, Roberto; Zhao, Zhitong; Zhang, Guihong (NanoEthics, 2025)
The central shortcoming of technological modernity has not been a lack of innovation, but rather the absence of categories capable of fostering questioning and difference—of sustaining, ultimately, an alterity: that which is other, not yet codified, non-hegemonic technology. This article begins with that thesis to develop a critical and situated hermeneutics of generative artificial intelligence (AI), arguing that dominant models reproduce an ontology without difference that symbolically forecloses the future of technology. Within this framework, the emerging LatamGPT project is analyzed as a form of peripheral technological dissent that, while it does not interrupt at its foundation a system oriented toward neutralizing difference, it does unsettle that system. The analysis unfolds in two main movements. The first diagnoses how cognitive biases and algorithmic automatisms, on the one hand, and global narratives of technological inevitability and progress—conceptualized here as forms of fallacy—on the other, cancel judgment and technocolonize plurality. The second shows how LatamGPT, by combining situated hermeneutic design, symbolic imagination, technodiversity, and the prioritization of the political dimension of technology in light of its structuring nature, reactivates the space for reappropriating technology from other symbolic and epistemological repertoires, opening an illuminating breach for alternative futures. Finally, the concept of technological alterity is introduced as an epistemic and political condition not only for imagining other ways of existing with technology, but also for resisting its dominant forms of closure, and as an inescapable task of any genuinely emancipatory philosophy of technology and critical thought.